DIFFERENTIAL RESPONSE OF CHICKPEA GENOTYPES GROWN UNDER NORMAL IRRIGATED AND DROUGHT STRESS CONDITIONS - RAHUL V. CHAHANDE; PAWAN L. KULWAL; LAXMAN B. MHASE; CHARUDATTA A. NIMBALKAR; GANESH D. KHALEKAR (The Bioscan, 2021)
Thirty two genotypes of chickpea were grown during rabi 2016-2017 under randomized block design (RBD) with two replications to evaluate response of chickpea genotypes under irrigated and drought stress conditions for mean values and various genetic parameters such as phenotypic (PCV), genotypic (GCV) coefficient of variation, heritability and genetic advance. Highly significant differences were observed between genotypes for all the traits under both the conditions. The values of studied traits significantly decreased in drought stress condition as compared to irrigated one. On the basis of mean performance studied, genotype Phule G-12113 was found to be least affected by drought stress condition, while genotypes NBeG-807 and Vishal were found to be highly sensitive to drought stress conditions. GCV and PCV for all characters under both conditions studied revealed that the PCV was higher than their corresponding GCV, indicating the influence of environment on the expression of these characters. Traits 100 seed weight and days to maturity showed high heritability coupled with high genetic advance. Therefore, result of the study suggest that characters 100 seed weight and days to maturity can be good selection criteria for improving seed yield per plant in chickpea for drought stress environments.